The Investigation of Soot Free Length of Jet Flame of Propane and Carbon Dioxide Gas Mixture. Issue 16 (10th December 2022) - Dou, Yuling; Tao, Changfa; Wang, Jingwu; Chu, Huaqiang; Hua, Yang; Liu, Xiaoyong
ABSTRACT: This study investigated the evolution of soot free length of turbulent jet flame with different mass flow rates of propane and carbon dioxide (CO2 ) experimentally. The nozzles with diameters of 2, 3, and 4 mm are used. The experimental results show that the soot free length increases with the increment in the concentration of CO2 since less soot will be produced, at the same time, soot free length fraction as the concentration of CO2 in the mixed fuel increases, it first shows a slight raise, and then increases rapidly. The correlation between modified Reynolds number and the soot free length has been developed. A correlation between soot free length fraction and the mixture fraction of propane and CO2 has been developed based on the analysis of laminar flame burning speed theory.